SNOWBALL THROWING SEBAGAI MODEL PEMBELAJARAN GUNA PENINGKATAN KEAKTIFAN BELAJAR SISWA MADRASAH IBTIDAIYYAH BIDANG MATEMATIKA - Umi Musaropah; Muhamad Mahali; Daluti Delimanugari; Muhammad Agus Najib; Mimi Indah Lestari; Muh. Nasruddin (Intersections, 2020)
Classroom action research was motivated by the less active attitude of the Class V students of MI Negeri 4 Gunungkidul. located in MI Negeri 4, located in Dusun Semenrejo, Pulutan Village, Wonosari District, Gunungkidul Regency in learning mathematics. The Snowball Throwing learning model is expected to be able to improve it, especially in the material of addition and subtraction of fractions with different denominators on. This research was conducted during July 2019. Data was collected through observation, interviews and documentation. The research was carried out for two sessions continuously to produce according to expectations where the achievement was achieved through learning as many as 22 students. Therefore it is suggested that the teacher can apply the SbT type of cooperative learning model to other materials. Variations can be made within the framework of cooperative learning that is adapted to the material and conditions